Pregunta
upstudy study bank question image url

Example 5 a) The \( n^{6} \) term of an exponential sequence (GP) is \( 2^{n} \). Calculate: i) the sum \( S_{4} \), of the first four terms of the sequence, ii) the sum of the sequence for large positive integral values of \( n \). b) The sum of the first \( n \) terms of a series is given by \( S_{n}=n(n+2) \). Find an expression for the \( n \)th term.

Ask by Lambert Stephens. in Ghana
Feb 13,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

a) i) The sum of the first four terms is 30. ii) The sum of the sequence grows without bound as n increases. b) The nth term is \( a_n = 2n + 1 \).

Solución

We are given two separate problems. Read carefully and proceed as follows. ────────────────────────────── Problem (a) We are told that the nth term of a geometric progression (exponential sequence) is   aₙ = 2ⁿ. Recall that in a geometric progression (GP) the nth term is usually given by   aₙ = a · r^(n–1). Here we see that 2ⁿ can be written as 2 · 2^(n–1). Thus the first term and common ratio are   a = 2  and  r = 2. (i) Sum of the first four terms, S₄: We have   a₁ = 2,   a₂ = 2² = 4,   a₃ = 2³ = 8,   a₄ = 2⁴ = 16. Therefore,   S₄ = 2 + 4 + 8 + 16 = 30. (ii) Sum of the sequence for large positive integral values of n: Since the common ratio r = 2 is greater than 1, the terms in the GP increase without bound. That is, as n increases the terms become larger and the partial sum grows indefinitely. Hence, the sum of the infinite sequence diverges (it does not approach a finite limit). ────────────────────────────── Problem (b) We are told that the sum of the first n terms of a series is given by   Sₙ = n(n + 2). To find an expression for the nth term, recall that the nth term aₙ can be found by subtracting the (n–1)th partial sum from the nth partial sum:   aₙ = Sₙ – Sₙ₋₁. Now, calculate Sₙ₋₁:   Sₙ₋₁ = (n – 1)[(n – 1) + 2] = (n – 1)(n + 1). Then,   aₙ = n(n + 2) – (n – 1)(n + 1). Expand each product:   n(n + 2) = n² + 2n,   (n – 1)(n + 1) = n² – 1      [using the difference of squares] Thus,   aₙ = (n² + 2n) – (n² – 1) = n² + 2n – n² + 1 = 2n + 1. ────────────────────────────── Final Answers a)  (i) S₄ = 30.  (ii) The sum diverges; that is, as n becomes very large, the sum increases without limit. b)  The nth term is aₙ = 2n + 1.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve part a, we recognize that the exponential sequence is defined by \( a_n = 2^n \), where \( a_1 = 2^1, a_2 = 2^2, a_3 = 2^3, \) and \( a_4 = 2^4 \). Calculating the first four terms yields: \( 2, 4, 8, \) and \( 16 \). The sum \( S_4 = 2 + 4 + 8 + 16 = 30 \). For large \( n \), the terms grow infinitely, so as \( n \) approaches infinity, the sum diverges. For part b, given that \( S_n = n(n + 2) \), to find the \( n \)th term, we use the relation \( T_n = S_n - S_{n - 1} \). First, calculate \( S_{n-1} \) which is \( (n - 1)(n + 1) \). Thus, the \( n \)th term is \( T_n = n(n + 2) - (n - 1)(n + 1) = n(n + 2) - (n^2 - 1) = 2n + 1 \). So, the \( n \)th term is \( 2n + 1 \).

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad